Epidemiology of Tourette Syndrome - Abdullah Yasir Yilmaz; Joseph Jankovic (Brain Sciences)
Background/Objectives: Tourette syndrome (TS) is a neurodevelopmental disorder, manifested by tics and a variety of behavioral comorbidities that cluster strongly within families, suggesting a combination of genetic and environmental risk factors. The underlying pathophysiology of TS remains to be elucidated. Understanding the incidence and prevalence across different populations provides valuable insights into the etiology and pathogenesis of the condition and aids in the development of effective treatment strategies. Methods: A comprehensive literature search was conducted on PubMed covering the period from 1 January 2000 to 1 January 2025. The search used the terms “Tourette syndrome”, “tics”, “tic disorders”, “epidemiology”, “prevalence”, and “incidence”. Results: The prevalence of TS is estimated to be about 1% in children and adolescents and approximately 0.01% in adults, with a male-to-female (M:F) ratio of about 4:1. The prevalence of tic disorders is higher in all studies performed in special education populations. Conclusions: Despite substantial methodological variability, our review of the literature indicates that TS is a relatively common neurobehavioral disorder, affecting nearly 1% of children, especially boys. Raising global awareness and expanding training in TS should lead to better identification of undiagnosed patients.